A pediatric desensitization protocol for etoposide. (7th February 2020) - Martinez, Nicole; Miyasaki, Ashley; Roh, Lucy; Koole, William; Fernandez, Karen S
Abstract: Purpose: The implementation of a pediatric desensitization protocol specific to etoposide in an adolescent with Hodgkin lymphoma is described. Summary: Etoposide is part of many chemotherapy regimens used to treat malignancies in children and adults, and it is also part of the backbone of many regimens used in clinical trials. Etoposide is known to produce hypersensitivity reactions during administration. Substitution with etoposide phosphate, which has less potential for hypersensitivity reactions, is used in place of etoposide after severe hypersensitivity reactions. Etoposide desensitization protocols (EDPs) have been reported in adult patients. Conclusion: The implementation of an etoposide desensitization protocol for pediatric patients is safe and helpful to prevent the elimination of etoposide from treatment protocols. The use of an EDP allowed the patient to remain on clinical trial and complete the prescribed treatment.